DIVERSIFICATION OF PROCESSED LEFTOVER RICE FOR SNACKSTO INCREASE INCOME FOR JOINT BUSINESS GROUPS INJAMI’AH ISLAM SHEIKH DAUD AL FATHONI (JISDA)THAILAND - Toni Hidayat; Marwang Hayeemaing; Junita Putri Rajana; Ardhansyah Putra; Ratna Sari Dewi; Dewi Nurmala; Ananda Gusty Firmansyah; Diva Yuana Putri (RADJA PUBLIKA, 2023)
International Community Service conducted abroad, precisely at Jami'ah Islam Syeikh Daud al-Fathoni Pattani Thailand is one of the efforts made by Universitas Muslim Nusantara Al Washliyah to implement a world class institute in developing the integrity and capability of lecturers in their role in carrying out educational, research, and community service tasks in order to implement knowledge in the midst of the world community. In Asian countries, rice is generally the main food consumed as a source of carbohydrates. Generally, rice cooked from rice usually requires a cooking time of around 20-30 minutes until the rice is cooked. To eat, rice is indeed more delicious if served fresh. However, there must be someone who has experienced excess rice when cooking so that it is not finished. Unfortunately, not everyone can use the leftover rice. So, many people just hoard it, even though the rice is not stale. In the daily lives of people, both in Indonesia and Thailand, it is often found that there is a lot of leftover rice that is wasted by people around the environment where they live. In fact, if you can process it, then something useful can be produced from the leftover rice. Entrepreneurship Training produces various products in the form of snacks by utilizing leftover rice, this is intended to provide learning space and capacity building, especially in entrepreneurship for students at the Ma'had Al-Bi'that Ad-diniyah Muang Campus, Yala Thailand, with various appropriate materials including providing an understanding so that business ideas develop, solving problems in starting a business and increasing motivation and self-confidence to start a business utilizing processed leftover rice. With the background of the partners, the theme taken in the International Community Service activity is: Mentoring for Entrepreneurship Introduction Activities with the title